Law, State and Telecommunications: institutional regulatory borders - Board, Editorial (Law, State and Telecommunications Review, 2013)
This article introduces the current issue of the Law, State, and Telecommunications Review by way of presenting its structure, contents, and editorial policy. Statutes and regulations issued in 2012 and pertaining to telecommunications are referred to in detail. It also addresses the main discussions that framed the political and legal landscape of the Brazilian telecommunications sector in the year before the publication of this volume.